Analisis Kemampuan Metaverse Untuk Inovasi Hospitality Industry Pariwisata di Masa Yang Akan Datang - Dina Fitriani; Febry Fatimah Azzahra; Reza Ardian Putra; Rifky Setiawan; Rigy Dyantika; Sifa Sukowati; Rizki Nurul Nugraha (Peneliti.net, 2023)
Metaverse is a virtual world that is currently very helpful for people to experience things that can't be done in person. The main purpose of this research is to find out the benefits of the metaverse that has been used so far in the tourism and hotel industries, find out what changes will occur in the future, and find out the opportunities and shortcomings of the metaverse in the tourism and hotel industries. The method used in this study is a qualitative method by collecting a number of books and magazines related to research. Metaverse has an impact on people's social life, but it will be very useful in the future